2018
DOI: 10.3390/ijms19061787
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 Interactors as Potential Therapeutic Targets for Cancer Treatment

Abstract: Signal transducers and activators of transcription (STATs) mediate essential signaling pathways in different biological processes, including immune responses, hematopoiesis, and neurogenesis. Among the STAT members, STAT3 plays crucial roles in cell proliferation, survival, and differentiation. While STAT3 activation is transient in physiological conditions, STAT3 becomes persistently activated in a high percentage of solid and hematopoietic malignancies (e.g., melanoma, multiple myeloma, breast, prostate, ova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
82
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(85 citation statements)
references
References 142 publications
(183 reference statements)
1
82
0
Order By: Relevance
“…As a result of the studies, STAT types have been found to have special functions (13). It has been reported that a large number of tumors are associated with increased activation levels of STATs, in particular with STAT3 and STAT5 (14)(15)(16)(17). In studies conducted on breast carcinomas, STAT activation has been shown to be associated with invasive breast carcinoma, not with benign and in situ carcinoma (18).…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the studies, STAT types have been found to have special functions (13). It has been reported that a large number of tumors are associated with increased activation levels of STATs, in particular with STAT3 and STAT5 (14)(15)(16)(17). In studies conducted on breast carcinomas, STAT activation has been shown to be associated with invasive breast carcinoma, not with benign and in situ carcinoma (18).…”
Section: Introductionmentioning
confidence: 99%
“…32 Study show that STAT3 becomes persistently activated in a high percentage of solid and hematopoietic malignancies. 39 NBT exhibited activity of inhibit cancer cells viability, migration and angiogenesis via regulating STAT3 expression. 40,41 Besides, the interaction between STAT3 and NF-kB plays a crucial role in the tumorigenesis, 32 targeting STAT3 and NF-kB offer new chemotherapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…breast, prostate, ovarian, and colon cancers), thus contributing to malignant transformation and progression which makes STAT3 an attractive therapeutic target for cancers. [57]there is also an evidence that studying gene expression of STAT1 , STAT2 and STAT3 gene can be useful for evaluating the efficacy of IFN treatment of the MS patients . [58] Our study is the first in silico analysis which based on functional and structural analysis while all other previous studies based on in vivo analysis, molecular analysis and genome sequencing [53,[59][60][61] This study revealed eleven Novel Pathological mutations have a potential functional impact and may thus be used as diagnostic markers for Job's syndrome.…”
Section: Discussionmentioning
confidence: 99%